Wildlife restoration in Nepal: tracking the conservation translocations in the country - Aryal, Chandra Mani; Aryal, Prakash Chandra (Journal of Environment Sciences, 2023)
Negative consequences of human impacts on biodiversity are undisputable and inadequate efforts in managing biodiversity have been realized across the globe. The present biodiversity crisis, including burgeoning effects of climate change, therefore, has warranted restoration actions in place. Conservation translocation, one of the effective measures of restoration, involves the individuals of species deliberate movement from one habitat to another, particularly animal species. Nepal has been practicing the conservation translocations for more than four decades. However, details of conservation translocation events and outcomes are not well documented. This article aims to explore the status and issues of conservation translocation in Nepal. For the purpose, we reviewed seven protected area management plans and nine species conservation action plans available in public domain along with related peer reviewed journal articles. We documented the conservation translocation of Blackbuck, Gharials, Swamp deer, Greater One Horned Rhino, Elongated tortoise, Narrow Headed Soft Shell Turtle, Wild Water Buffalo and Vulture. Adoption of feeble adaptive management framework and ad hoc approach of wildlife translocation has left many rooms for improvement in the translocation strategies of Nepal. This is largely exemplified by the improvement required in Vulture Breeding Center, Swamp deer and Wild water buffalo translocations to Chitwan National Park, and Blackbuck translocation to Bardia National Park. For many species, data and information are limited to evaluate the wildlife restoration outcomes independently.